Lessons and Insights from CCAFS Results-Based Management Trial - Schuetz, Tonya; Förch, Wiebke; Schubert, Cecilia; Thornton, Philip K.; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Lessons learned from Flagship 4's Results-Based Management trial, based of an extensive survey to the trial project managers, coordinators and partners.